(untitled) (ETIMA, 2024)
This paper deals with the energy mix of the Slovak Republic with a focus on renewable energy sources and their development in recent years. The share of renewable energy sources in electricity production in Slovakia rose from 310 GWh in 2011 to 2 380 GWh in 2021. This number does not include hydro energy, which has had a very good position in Slovakia for many years and its installed capacity is almost unchanged, in 2021 it was 2 546 MW, and electricity production was at about 4 600 GWh. The energy sector in Slovakia, as well as in other European countries, must reflect worldwide changes and challenges. It needs to consider problems in many fields, such as technical, economic, ecological, legislative, social, and political. The current situation in the Slovak energy system is described with a focus on energy dependence and the usage of renewables. Some energy statistics are shown in this paper. Finally, possible scenarios and plans for the reduction of energy dependence are discussed.